Jack and the beanstalk - Down, Hayley; Page, Nick; Saunders, Katie (Make Believe Ideas, Ltd., Berkhamsted, Herts (England), 2011, 2011)
A boy climbs to the top of a giant beanstalk where he uses his quick wits to outsmart a giant and make his and his mother's fortune
English stories
Keywords: Children's stories